2010
DOI: 10.1155/2010/786078
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Foxp3+Cells by Depletion with the PC61 mAb Induces Mortality in Resistant BALB/c Mice Infected withToxoplasma gondii

Abstract: Regulatory T cells (Tregs) are CD4+Foxp3+ cells that modulate autoimmune responses. Tregs have been shown to be also involved during the immune response against infectious agents. The aim of this work is to study the role of Tregs during the infection with the intracellular protozoan Toxoplasma gondii. Resistant BALB/c mice were injected with 200 μg of anti-CD25 mAb (clone PC61) and 2 days later they were infected with 20 cysts of the ME49 strain of T. gondii. We observed that depleted mice showed 50–60% morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
1
27
1
Order By: Relevance
“…Neither the number nor the frequency differed from that in the naive control group. A lack of Treg reduction seemed to contradict the uncontrolled immune response observed in the RH group and previous studies (14,18), showing that a decrease in Tregs was associated with mortality. However, we cannot exclude the possibility that this decrease appeared just before death or that it was significant only at the local site.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Neither the number nor the frequency differed from that in the naive control group. A lack of Treg reduction seemed to contradict the uncontrolled immune response observed in the RH group and previous studies (14,18), showing that a decrease in Tregs was associated with mortality. However, we cannot exclude the possibility that this decrease appeared just before death or that it was significant only at the local site.…”
Section: Discussioncontrasting
confidence: 54%
“…Type I strains are uniformly lethal except after attenuation, which leads to lower levels of replication and dissemination in the host and the development of long-term immunity, as for type II strains. Several studies have been performed to examine the role of Tregs using a susceptible C57BL/6 mouse strain (14,17,18,20) and a type II Toxoplasma strain. Decreased Foxp3 ϩ Treg counts at local and systemic sites were associated with such mortality in C57BL/6-susceptible mice after lethal oral infection with the type II strain (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that despite the strikingly higher LP parasite burden in Treg cells depleted BALB/c mice, it was still considerably lower than the parasite burden seen in this tissue in B6 mice during acute infection. This may partially explain the acute phase survival of Treg cells depleted BALB/c mice in our study, although a previous study reported partial acute phase mortality after T. gondii ME49 strain infection of Treg cells depleted BALB/c mice [37]. Additional support for a protective role of Treg cells in T. gondii infection was obtained from the findings that BALB/c mice depleted for Treg cells had a strikingly higher brain parasite cyst burden, as opposed to non-treated mice.…”
Section: Discussionmentioning
confidence: 53%